Enjeux méthodologiques de l’émergentisme pour la recherche en acquisition et en didactique des langues - Heather E. Hilton (Recherches en didactique des langues et des cultures)
Emergence is a concept which, like many others in the Social Sciences, comes to us via Life and Earth Sciences, and can be traced back to Darwinian theory on species evolution. In this article, we look at the route taken by the concept of emergence in language acquisition research, and summarize its contribution to second language acquisition (SLA) theory. We will also describe methodological implications of an Emergentist perspective on language teaching, and will sketch a few recommendations for pedagogical research.